PERAN CORPORATE SOCIAL RESPONSIBILITY DALAM MEMEDIASI HARGA SAHAM PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PADA TAHUN 2018-2021 - Sigit Gunawan; Nugroho Mardi Wibowo; Hadi Susanto (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
The purpose of this study is to describe the condition of financial ratios which include profitability ratios, company size and leverage, Corporate Social Responsibility and stock prices in Consumer Goods Industry Companies listed on the IDX in 2018-2021. To analyze and prove the effect of profitability, company size and leverage on Corporate Social Responsibility. To analyze and prove the effect of financial ratios on profitability, company size, and leverage as well as Corporate Social Responsibility on stock prices. To analyze and prove that Corporate Social Responsibility can mediate the effect of financial ratios on profitability, company size and leverage indirectly on stock prices. The population used in this research is 51 consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The sampling technique used purposive sampling so that 11 companies were obtained as research samples. Methods of data analysis using PLS. Based on the results of the study, it was found that the ROA level, company size, leverage and stock price were also not good. Profitability financial ratios and company size have a significant effect on Corporate Social Responsibility, financial leverage ratios have no significant effect on Corporate Social Responsibility. Financial ratios of profitability and Corporate Social Responsibility have no significant effect on stock prices. Financial ratios of company size and leverage have a significant effect on stock prices. Financial ratios of profitability and company size and leverage have no significant effect on stock prices mediated by Corporate Social Responsibility.